Repulsive Osmotic Delamination: 1D Dissolution of 2D Materials. Issue 3 (6th November 2022) - Dudko, Volodymyr; Khoruzhenko, Olena; Weiß, Sebastian; Daab, Matthias; Loch, Patrick; Schwieger, Wilhelm; Breu, Josef
Abstract: 2D materials have proved their potential in nearly every area of material science and chemistry. Unfortunately, large‐scale production of nanosheets is not straightforward. Current methods suffer from low yield, uncontrollable defects, and requires a high‐energy input. There is always a tradeoff between high quality and high yield. In this review, the alternative is highlighted to existing methods of 2D nanosheet production – 1D dissolution, historically known as osmotic swelling. As a thermodynamically driven, and therefore spontaneous, process it provides numerous benefits such as high aspect ratio and defect‐free nanosheets with a quantitative yield. In this review, the theory behind this process is discussed, compare it with the existing methods, and highlight the key features that allow to extend 1D dissolution to different charged layered materials. Moreover, the applications in which nanosheets obtained by 1D dissolution proved to be advantageous due to their unique, processing‐related features are discussed. Abstract : 2D materials are of huge interest in all areas of material science and modern technologies. What if it could produce any 2D nanosheets with the 100% yield without any additional energy required? In this review article, the concept of delamination by 1D dissolution and its application for 2D materials is introduced.